solve and check your answer-

a. x=4/5(x+10)

b. 2y+5/3=26/3-y

(A) x = 4/5*(x + 10)

=> x = 4x/5 + 8

=> x - 4x/5 = 8

=> (5x - 4x)/5 = 8

=> x = 8 * 5 = 40

Verification / Checking-

LHS = x = 40

RHS = 4/5*(x + 10) = 4/5*(40 + 10) = 4/5 * 50 = 40

. .. LHS = RHS

Thus, verified/checked.

(B) 2y + 5/3 = 26 /3 - y

=>2y + y= 26/3 - 5/3

=> 3y = (26-5)/3

=>y = 7/3

__-__

**Verification / check**LHS = 2y + 5/3 = 2* 7/3 + 5/3 = 14/3 + 5/3 = 19/3

RHS = 26/3 - y = 26 /3 - 7/3 = 19/3

**Since, LHS = RHS**

**Thus, verified.**
**
**